2020
DOI: 10.1038/s41598-020-60694-z
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing Electrocochleography as a Microphone for Fully Implantable Cochlear Implants

Abstract: current cochlear implants (cis) are semi-implantable devices with an externally worn sound processor that hosts the microphone and sound processor. A fully implantable device, however, would ultimately be desirable as it would be of great benefit to recipients. While some prototypes have been designed and used in a few select cases, one main stumbling block is the sound input. Specifically, subdermal implantable microphone technology has been poised with physiologic issues such as sound distortion and signal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…It should be noted that given that the ECochG response is comprised of both cochlear and auditory nerve responses, simply calculating a differential curve does not result in complete isolation of hair cell response [see Forgues et al (2014) for in-depth review]. Riggs et al (2020) described this approach in a preliminary study and here we have expanded upon this approach with the addition of more participants. The SSIM is a mathematical model designed to compare two images (e.g., spectrograms) and determine their overall similarity based on three domains: luminance (intensity), contrast, and structure (contour) (Wang and Bovik 2002; Wang et al 2004).…”
Section: Methodsmentioning
confidence: 99%
“…It should be noted that given that the ECochG response is comprised of both cochlear and auditory nerve responses, simply calculating a differential curve does not result in complete isolation of hair cell response [see Forgues et al (2014) for in-depth review]. Riggs et al (2020) described this approach in a preliminary study and here we have expanded upon this approach with the addition of more participants. The SSIM is a mathematical model designed to compare two images (e.g., spectrograms) and determine their overall similarity based on three domains: luminance (intensity), contrast, and structure (contour) (Wang and Bovik 2002; Wang et al 2004).…”
Section: Methodsmentioning
confidence: 99%
“…6(b)). 201 Recently, it was reported that the insertion of the Utah electrode array into the human occipital cortex can evoke visual perception (Fig. 6(c)).…”
Section: The Function Of Nerve Regulation and Stimulationmentioning
confidence: 98%
“…198 (b) The most successful of the sensory implants is the cochlear implant, which has restored the hearing of the deaf. 201 (c) Stimulation of electrode arrays in the occipital cortex can evoke visual perception. 202 (d) DBS can effectively treat dyskinesia by stimulating nerve tissue at high frequency.…”
Section: Application Of Implantable Neural Electrodes In Neural Inter...mentioning
confidence: 99%
“…Apart from requiring functionally intact middle and external ears, the insertion of an additional component within the confined intracochlear space remains problematic. In order to overcome this limitation, Riggs et al [40 ▪ ] proposed to measure cochlear microphonic responses produced by the outer hair cells using the already existing cochlear implant-electrocochleography (CI-ECochG) technology. This ‘biological microphone’ would not require any additional sensors, since a portion of the electrode array itself could be used to obtain ECochG responses.…”
Section: Implantable Microphonesmentioning
confidence: 99%